EPIDEMIOLOGICAL CONTACT (EPICONTACT) INVESTIGATION OF COVID-19 AT ISLAMIC BOARDING SCHOOLS IN KUNINGAN REGENCY, INDONESIA - Cecep Heriana; Faridah Binti Moh. Said; Farzana Yasmin; Dieta Nurrika; Purwo Setiyo Nugroho (Universitas Airlangga, 2023)
Introduction: COVID-19 has spread throughout the world with more than 61, 27 million patients infected, including in education clusters that implement boarding schools. Contact investigations on the cluster are necessary to control the spread of the virus. Aims: To describe the epidemiological contact pattern of investigation results in the Islamic Boarding School cluster in Kuningan Regency. Methods: The design of this study is descriptive with epidemiological approach. The population is all students of Pondok Pesantren X, as many as 164 students, a sample of 157 students who are positive for COVID-19, and research instrument for the COVID-19 outbreak is investigation form, the variables studied included age, gender, symptoms, duration of contact, number of contacts, number of contact groups and place of contact. Result: Univariate data analysis with epi-contact analysis show: sex: 33.3% male, 60.03% female, average age 15.05 years, the average number of contacts 3.25 people, the average number of male contacts 2.62 and female 3.39, number of male contact groups 41, number of female contact groups 91. Age of value p=0.037. Conclusions: Contact pattern conclusions are mostly in female with the number of contacts between 3-4 people and age is related to the number of contacts. Limiting contact when there is suspicion is necessary to prevent transmission.